2009
DOI: 10.1152/ajplung.90488.2008
|View full text |Cite
|
Sign up to set email alerts
|

NOX4 mediates hypoxia-induced proliferation of human pulmonary artery smooth muscle cells: the role of autocrine production of transforming growth factor-β1 and insulin-like growth factor binding protein-3

Abstract: Persistent hypoxia can cause pulmonary arterial hypertension that may be associated with significant remodeling of the pulmonary arteries, including smooth muscle cell proliferation and hypertrophy. We previously demonstrated that the NADPH oxidase homolog NOX4 mediates human pulmonary artery smooth muscle cell (HPASMC) proliferation by transforming growth factor-beta1 (TGF-beta1). We now show that hypoxia increases HPASMC proliferation in vitro, accompanied by increased reactive oxygen species generation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
147
4
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(165 citation statements)
references
References 72 publications
10
147
4
4
Order By: Relevance
“…NOX4 is the predominant homolog expressed in human lung microvascular and human pulmonary arterial endothelial cells compared with NOX1, NOX2, NOX3, or NOX5 (338). Inflammatory stimuli LPS, TNF a, hyperoxia, TGF-b, and hypoxia were demonstrated to enhance ROS generation via NOX4 (29,191,242,295,335,338). The expression of intercellular adhesion molecule-1 (ICAM-1), IL-8, and MCP-1 in endothelial cells in response to LPS was demonstrated to be dependent on NOX4 activation (335).…”
Section: A Nadph Oxidase-derived Ros In Inflammationmentioning
confidence: 99%
“…NOX4 is the predominant homolog expressed in human lung microvascular and human pulmonary arterial endothelial cells compared with NOX1, NOX2, NOX3, or NOX5 (338). Inflammatory stimuli LPS, TNF a, hyperoxia, TGF-b, and hypoxia were demonstrated to enhance ROS generation via NOX4 (29,191,242,295,335,338). The expression of intercellular adhesion molecule-1 (ICAM-1), IL-8, and MCP-1 in endothelial cells in response to LPS was demonstrated to be dependent on NOX4 activation (335).…”
Section: A Nadph Oxidase-derived Ros In Inflammationmentioning
confidence: 99%
“…Nox4 appears to generate H 2 O 2 , although the primary product is probably O 2 -, which is rapidly dismutated to H 2 O 2 (202,232). Nox4 contributes to basal ROS production through its constitutive activity and to increased ROS generation when induced by Ang II, glucose, tumor necrosis factor a, and growth factors (90,127). Recent studies have identified a 28-kDa Splice Variant of Nox4 located in the nucleus of vascular cells, which may be important in pathophysiologic effects through modulation of nuclear signaling and DNA damage (9).…”
Section: Nox4mentioning
confidence: 99%
“…Several signaling pathways are associated with the growth and apoptosis of PASMCs during PAH (12,13). For example, stimulation of human PASMCs with platelet-derived growth factor induced PI3K-dependent activation of Akt, p70 S6 kinase and ribosomal protein S6, suggesting that PI3K signaling is necessary to mediate human PASMCs proliferation and the activation of PI3K may play an important role in vascular remodeling (14).…”
Section: Discussionmentioning
confidence: 99%